2012
DOI: 10.1530/eje-12-0651
|View full text |Cite
|
Sign up to set email alerts
|

Genotypes in relation to phenotypic appearance and exposure to environmental factors in Graves' hyperthyroidism

Abstract: Background: Genetic polymorphisms and environmental factors are both involved in the pathogenesis of Graves' disease, but their interaction and effect on Graves' phenotypes have scarcely been investigated. Objective: To test the hypothesis that subjects with susceptibility genotypes develop more severe Graves' hyperthyroidism at a younger age and after less exposure to environmental factors, with attention to gender differences. Study design: A prospective observational multicenter study in 205 adult Caucasian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 33 publications
3
5
0
Order By: Relevance
“…While we have managed to extend the list of POGD risk loci , we also confirmed the previously reported association between the CTLA4 polymorphism and POGD . In general, the results of our study suggest that POGD and AOGD share multiple common genetic risk variants, which is also in line with most findings from studies comparing adults with early‐ and late‐onset GD . Moreover, we showed that the effect sizes for the identified risk variants are similar in POGD and AOGD.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…While we have managed to extend the list of POGD risk loci , we also confirmed the previously reported association between the CTLA4 polymorphism and POGD . In general, the results of our study suggest that POGD and AOGD share multiple common genetic risk variants, which is also in line with most findings from studies comparing adults with early‐ and late‐onset GD . Moreover, we showed that the effect sizes for the identified risk variants are similar in POGD and AOGD.…”
Section: Discussionsupporting
confidence: 91%
“…The PTPN22 gene encodes a lymphoid‐specific protein tyrosine phosphatase (LYP), which is a negative regulator of T cell activation, while the analysed missense variant (rs2476601) confers an increased susceptibility to a number of autoimmune disorders . For both loci , MAGI3 and PTPN22 , an association with age of GD onset has been already shown in our previous studies, while these findings were not replicated in other cohorts . Here, we confirmed our previous results.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations